Evaluation of white grain maize varieties for growth, yield and yield components - Bastola, Arjun; Soti, Ankit; Pandey, Utshav; Rana, Mausami; Kandel, Manoj; Shrestha, Jiban (Journal of Agriculture and Natural Resources, 2021)
Maize (Zea mays L.) is one of the most commonly cultivated crop after rice in Nepal. The present study was done to evaluate and recommend the best performing white maize genotypes in mid hill region of Nepal. This study was conducted at research field of Kavre, Nepal during the rainy season of 2019. Five white maize genotypes were evaluated in randomized complete block design with four replications where Deuti used as standard check. Ear and plant height of plant, days to 50% silking and tasseling, count of leaf above and below main cob, total number of leaf, cob length, cob diameter, kernel rows per cob, kernels count per row, thousand kernels weight, shelling and sterility percentage, stay green and grain yield parameters were observed. Deuti and DMH-7314 had good stay green and husk cover rating. Plant height (282.6 cm) and ear height (162.4 cm) was more in HB-008. Number of kernels per row was more in HB-008 (36.5) and HB-007 (36.5) and thousand kernel weights was more in DMH-7314 (386.3 g) followed by Deuti (353.9 g). DMH-7314 was late in tasseling (86 days) and silking (89 days) but shelling percentage was lowest in DMH-7314 (70.8) than other varieties. Analysis of variance reveled that genotype HB-008 (9.70 t/ha) as compared to standard check Deuti (7.80 t/ha). Thus genotype HB-008 perform better in mid hill region of Kavre, Nepal.